Intercellular communications in multispecies oral microbial communities - Guo, Lihong; He, Xuesong; Shi, Wenyuan (Frontiers in Microbiology, 2014)
The oral cavity contains more than 700 microbial species that are engaged in extensive cell-cell interactions. These interactions contribute to the formation of highly structured multispecies communities, allow them to perform physiological functions, and induce synergistic pathogenesis. Co-adhesion between oral microbial species influences their colonization of oral cavity and effectuates, to a large extent, the temporal and spatial formation of highly organized polymicrobial community architecture. Individual species also compete and collaborate with other neighboring species through metabolic interactions, which not only modify the local microenvironment such as pH and the amount of oxygen, making it more suitable for the growth of other species, but also provide a metabolic framework for the participating microorganisms by maximizing their potential to extract energy from limited substrates. Direct physical contact of bacterial species with its neighboring co-habitants within microbial community could initiate signaling cascade and achieve modulation of gene expression in accordance with different species it is in contact with. In addition to communication through cell-cell contact, quorum sensing (QS) mediated by small signaling molecules such as competence-stimulating peptides (CSPs) and autoinducer-2 (AI-2), plays essential roles in bacterial physiology and ecology. This review will summarize the evidence that oral microbes participate in intercellular communications with co-inhabitants through cell contact-dependent physical interactions, metabolic interdependencies, as well as coordinative signaling systems to establish and maintain balanced microbial communities.